Fuel cells : principles, design, and analysis - Revankar, Shripad T.; Majumdar, Pradip, 1954- (Boca Raton : CRC Press,Taylor & Francis Group, 2014)
"This book covers all essential themes of fuel cells ranging from fundamentals to applications. It includes key advanced topics important for understanding correctly the underlying multi-science phenomena of fuel cell processes. The book does not only cope with traditional fuel cells but also discusses the future concepts of fuel cells. The book is rich on examples and solutions important for applying the theory into practical use.""--Peter Lund, Aalto University, Helsinki""A good introduction to the range of disciplines needed to design, build and test fuel cells.""-Nigel Brandon, Imperial Co.
Introduction Primary Energy Sources-Fossil Fuel Renewable Energy Resources and Alternative Energy Systems Electrochemical Device-Basic Components and Operation Basic Components and Operation of a Fuel Cell Classification and Types of Fuel Cell Applications of Fuel Cell References Review of Electrochemistry Electrochemical and Electrolysis Cell Oxidation and Reduction Processes Faraday's Laws Ideal Polarized Electrode Polarization and Overpotential Conductivity and Ohm's Law Mass Transport and Nernst-Planck Equation Standard Hydrogen and Other Reference Electrode Cyclic Voltammetry References Reviews of Thermodynamics State, Phase, and Properties Thermodynamic Process and Cycle Ideal Gas Equation of State Energy and Energy Transfer The Conservation of Mass The First Law of Thermodynamics The Second Law of Thermodynamics Thermodynamic Relations Specific Heat Estimation of Change in Enthalpy, Entropy, and Gibbs Function for Ideal Gases Mixture of Gases Combustion Process Enthalpy of Formation hf ( 0 ) First Law for Reacting Systems Enthalpy of Combustion (hRP) Temperature of Product of Combustion Absolute Entropy sf ( 0 ) Gibbs Function of Formation gf ( 0 ) References Thermodynamics of Fuel Cell Conventional Power Generation-Heat Engine Energy Conversion in Fuel Cell Changes in Gibbs Free Energy Effect of Operating Conditions on Reversible Voltage Fuel Cell Efficiency Fuel Consumption and Supply Rates Water Production Rate Heat Generation in a Fuel Cell Summary References Electrochemical Kinetics Electrical Double Layer Electrode Kinetics Single- and Multistep Electrode Reactions Electrode Reaction in Equilibrium-Exchange Current Density Equation for Current Density-The Butler-Volmer Equation Activation Overpotential and Controlling Factors Tafel Equation-Simplified Activation Kinetics Relationship of Activation Overpotential with Current Density-Tafel Plots Fuel Cell Kinetics Fuel Cell Irreversibilities-Voltage Losses Fuel Cell Polarization Curve Summary References Heat and Mass Transfer in Fuel Cell Fluid Flow Heat Transfer in Fuel Cell Mass Transfer in Fuel Cell Diffusion Coefficient Mass Transfer Resistance in Fuel Cell Summary References Charge and Water Transport in Fuel Cell Charge Transport Solid-State Diffusion Charge Conductivity Ohmic Loss in Fuel Cell Water Transport Rate Equation Summary References Fuel Cell Characterization Characterization of Fuel Cell and Fuel Cell Components Electrochemical Characterization Techniques Characterization of Electrodes and Electrocatalysts Characterization of Membrane Electrode Assembly Characterization of Bipolar Plates Characterization of Porous Structures of Electrodes and Membranes Fuel Cell Test Facility Summary References Fuel Cell Components and Design Alkaline Fuel Cell Phosphoric Acid Fuel Cell Polymer Electrolyte Membrane Fuel Cell Molten Carbonate Fuel Cell Solid Oxide Fuel Cell Direct Methanol Fuel Cell References Fuel Cell Stack, Bipolar Plate, and Gas Flow Channel Fuel Cell Stack Design Fuel Cell Stack and Power System Water Removal and Management Cooling/Heating System for Fuel Cells Bipolar Plate Design Gas Flow Field References Simulation Model for Analysis and Design of Fuel Cell Zero-Order Fuel Cell Analysis Model One-Dimensional Fuel Cell Analysis Model One-Dimensional Water Transport Model One-Dimensional Electrochemical Model One-Dimensional Fuel Cell Thermal Analysis Model A Simplified One-Dimensional Heat Transfer Model Multi-Dimensional Model References Dynamic Simulation and Fuel Cell Control System Dynamic Simulation Model for Fuel Cell Systems Simulation of Fuel Cell-Powered Vehicle Dynamic Simulation of Integrated Fuel Cell Systems Control System References Fuel Cell Power Generation Systems Fuel Cell Subsystems Fuels and Fuel Processing Hydrogen as Energy Carrier Summary References Fuel Cell Application, Codes and Standards, and Environmental Effects Fuel Cell Applications Fuel Cell Codes and Standards Environmental Effects Summary References Nomenclature Appendices Index
engineering bookfair2015
Includes bibliographical references and index.
Keywords: Fuel cells; SCIENCE / Energy; TECHNOLOGY & ENGINEERING / Environmental / General; SCIENCE / Mechanics / Dynamics / Thermodynamics